Ocurrencia de enemigos naturales de thrips palmi karny (Thysanoptera: Thripidae) en cultivos - Vazquez, L.L.=700 1 Rodriguez, E.; Blanco, E.; De la Torre, P.
(Es, En)
Ilus., 9 ref.
Keywords: THRIPS PALMI; THYSANOPTERA; ENEMIGOS NATURALES; CULTIVOS; CUBA